Assessment of Occupational Exposure to Bisphenol A in Five Different Production Companies in Finland. Issue 1 (1st January 2017) - Heinälä, Milla; Ylinen, Katriina; Tuomi, Tapani; Santonen, Tiina; Porras, Simo P.
Abstract: The aim of the study was to assess occupational exposure to bisphenol A in Finland. Five companies took part in the research project: two paint factories (liquid and powder paints), a composite product factory, a thermal paper factory, and a tractor factory. Exposure was assessed by measuring total bisphenol A excretion (free and conjugated) from urine samples, and its concentrations in the air. The results revealed the specific work tasks in two of five companies in which significant occupational exposure to bisphenol A may occur. In the manufacturing of liquid paint hardener, urine samples collected after the working day showed bisphenol A levels of up to 100–170 µg l −1 . Workers in thermal paper manufacturing were also exposed to bisphenol A, especially those working in the manufacture of coating material and operating coating machines. Median concentrations of the post-shift urine samples of coating machine workers were in the range of 130–250 µg l −1 . The highest bisphenol A concentrations were in the range of 1000–1500 µg l −1 . Recommendations for more effective personal protection resulted in decreased exposure, particularly among coating machine operators. In the rest of the companies, urinary bisphenol A levels were typically in the range of those of the general population. Bisphenol A concentrations in air samples were typically low (<40 µg m −3 ), except in some short-term duties related to the handling of solid bisphenol A (maximum 17.6 mg m −3 ). Low air levels, even in the companies with high urinary levels, suggest exposure via dermal contact. According to the results, exposure to bisphenol A may occur particularly in work tasks that involve the use of pure bisphenol A. In these tasks, special attention should be paid to the prevention of skin exposure. Inhalation exposure may become relevant in dusty work tasks. Since skin exposure is of potential concern in these tasks, biomonitoring is recommended as the method for assessing occupational exposure to bisphenol A.